2004
DOI: 10.1039/b313139d
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted free radical chemistry using the persistent radical effectElectronic Supplementary Information (ESI) available: experimental procedures and analytical data for all the described compounds. See http://www.rsc.org/suppdata/cc/b3/b313139d/

Abstract: Environmentally benign radical carboaminoxylations of various nonactivated olefins and difficult radical cyclization reactions are performed in good to excellent yields and with short reaction times under microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 16 publications
(7 reference statements)
0
29
1
2
Order By: Relevance
“…[197] Wetter and Studer have described radical carboaminoxylations of various nonactivated olefins and difficult radical cyclizations (Scheme 40). [198] Scheme 37. Microwave-assisted glycosylation reactions.…”
Section: Radical Reactionsmentioning
confidence: 99%
“…[197] Wetter and Studer have described radical carboaminoxylations of various nonactivated olefins and difficult radical cyclizations (Scheme 40). [198] Scheme 37. Microwave-assisted glycosylation reactions.…”
Section: Radical Reactionsmentioning
confidence: 99%
“…Repeating the ATRC reaction of 3 for 120 h in refluxing toluene resulted in the total consumption of both ester 3 and the lactone 4, and the formation of 1-chloronaphthalene (6), which was isolated [14] in 23 % yield after column chromatography. Moreover we were delighted to observe that irradiation [15][16][17] of a solution of the ester 3 in 1,2-dichloroethane containing our standard catalyst system in a microwave reactor [18] afforded 6 in 84 % yield after a much reduced reaction time of two hours (Scheme 1).Wishing to establish the synthetic generality of this reaction, we subjected a variety of readily available aryl trichloroacetates (8, 10, 12 a-12 f; Scheme 2) to the same experimental protocol and found that, in each case, benzannulation proceeded smoothly over two hours at 200 8C to produce their respective naphthalene derivatives. The requisite ortho-allyl phenols used in this study are themselves readily available from an ortho-Claisen rearrangement [19] of their respective allyl aryl ethers, a process which in many cases can also be efficiently accomplished in a microwave reactor.…”
mentioning
confidence: 99%
“…These unusual properties have led to a wide range of applications spanning their use in biology as spin labels [1][2][3][4][5][6] to the development of organomagnetic materials. 7 In organic chemistry, nitroxides have been used in kinetic studies, [8][9][10][11] as oxidizing species in the form of the corresponding N-oxo ammonium salts, [12][13][14][15][16][17][18][19][20][21][22][23] as temporary caps for transient carbon radicals, [24][25][26][27][28][29][30][31] and as probes for stereocontrol with prochiral carbon radicals. [32][33][34][35][36] In polymer chemistry, nitroxide-mediated polymerization (NMP) [37][38][39][40][41][42][43][44][45][46][47] has become popular as a method for preparing living polymers ...…”
Section: Introductionmentioning
confidence: 99%